Safety, tolerability, and immunogenicity of a novel 4-antigen Staphylococcus aureus vaccine (SA4Ag) in healthy Japanese adults - Megumi Inoue; Takuma Yonemura; James Baber; Yasuko Shoji; Masakazu Aizawa; David Cooper; Joseph Eiden; William C. Gruber; Kathrin U. Jansen; Annaliesa S. Anderson; Alejandra Gurtman (Human Vaccines & Immunotherapeutics, 2018)
A novel Staphylococcus aureus 4-antigen vaccine (SA4Ag) is under development, comprising capsular polysaccharide serotypes 5 and 8 (CP5 and CP8) conjugated to CRM197, recombinant protein clumping factor A (rmClfA), and recombinant manganese transporter protein C (MntC). We evaluated SA4Ag safety, tolerability, and immunogenicity in Japanese adults aged 20 to 64 and 65 to 85 years. A total of 136 healthy Japanese adults (68 per age group) were randomized 1:1 to receive single-dose SA4Ag or placebo intramuscularly (Day 1). Safety assessments included reactogenicity and adverse events. The ability of the vaccine to induce immune responses that are considered functional due to their ability to facilitate the killing of S. aureus or neutralize S. aureus virulence mechanisms was assessed using 5 different antigen-specific assays. SA4Ag was well tolerated in both age groups, with no safety concerns. At Day 29, > 85% of SA4Ag recipients in each age group achieved predefined thresholds for each antigen. Antibody geometric mean-fold rises from baseline to Day 29 in SA4Ag groups were: > 80 and > 30 for CP5 and CP8 (opsonophagocytic activity assay), > 10 for ClfA (fibrinogen-binding inhibition assay), and > 15 and > 7 for ClfA and MntC (competitive Luminex® immunoassay), respectively. Antibody titers decreased through Month 12 but remained well above baseline and placebo levels. SA4Ag had an acceptable safety profile and induced rapid and robust functional immune responses in both age groups. These results support ongoing development of SA4Ag for the prevention of invasive S. aureus disease in elective-surgery patients in Japan, North America, and Europe.